Addressing child-to-parent violence: developmental and intervention considerations. Issue 1 (2nd January 2022) - Curtis, Ashlee; Harries, Travis; Moulds, Lauren; Miller, Peter
ABSTRACT: Child-to-parent violence (CPV) is any form of emotional or physical violence used by a child or adolescent toward a parent/caregiver. Social learning based interventions are offered to families experiencing CPV. However, it is not currently known how younger CPV users may respond to interventions originally targeted toward older adolescents, and if there are unique criminogenic risk factors and needs for early-onset CPV. The current paper is a narrative review of CPV in respect to key considerations for interventions for this population. The current review found that early-onset CPV users (10 and 11 years old) may be more likely to possess callous–unemotional (CU) traits and use proactive aggression. This population may be reward dominant, insensitive to punishment, and show deficits in emotion recognition. Consequently, younger CPV users with high CU traits may have worse intervention outcomes than low CU CPV users, in social learning programmes. To adapt, interventions facilitating younger CPV users should consider programmes which are longer in duration, reward-based, and target empathy development, parental warmth, and mentalizing skills. Teaching positive outcomes for non-aggression, and closely monitoring peer feedback should also be a priority. Finally, interventions should make adaptions to address developmental limitations in language and metacognition.